Pendidikan anti korupsi sebagai upaya membangun generasi berintegritas - Hidayatullaili, Amelia Septi Septi (Maliki Interdisciplinary Journal, 2026)
Corruption poses a serious threat to the life of the nation and state in Indonesia because it harms state finances, undermines social order, and undermines public trust in the government. Eradication efforts, which have focused on law enforcement, need to be complemented by ongoing prevention through anti-corruption education as a step towards building a generation with integrity. This paper examines the role of anti-corruption education in instilling the values of honesty, responsibility, discipline, justice, simplicity, and the courage to reject fraud as part of students character. Anti-corruption education is seen as a vehicle for Pancasila based moral formation while strengthening national identity and national resilience. However, its implementation remains hampered by an incomplete curriculum, limited teacher competency, and weak daily behavioural habits. Through a literature review and policy analysis, this paper recommends the systematic integration of anti-corruption education into the curriculum, school culture, and campus environment to produce a young generation with integrity, high moral awareness, and the courage to realize clean and just state governance.